Principles of welding : processes, physics, chemistry, and metallurgy - Messler, Robert W., Jr., 1942- (Wiley-VCH, 2004)
An advanced yet accessible treatment of the welding process and its underlying science. Despite the critically important role welding plays in nearly every type of human endeavor, most books on this process either focus on basic technical issues and leave the science out, or vice versa. In Principles of Welding, industry expert and prolific technical speaker Robert W. Messler, Jr. takes an integrated approach--presenting a comprehensive, self-contained treatment of the welding process along with the underlying physics, chemistry, and metallurgy of weld formation. Promising to bec.